A socio-legal analysis of collective identity construction in social movements - Lucia Irene Lapenta (Sortuz)
This paper aims to analyze the processes of identity formation comprised within social movement actions. The case of the 8-N movement occurred in 2012 in Argentina is used as a central example of a collective identity formation through the use of new technologies in favor of political activism. The theoretical approach to this topic contains a convergence of notions coming from Social Movement Studies and from Political Studies. I take certain notions from Action-Identity Theory regarding social movements’ doctrine. Regarding political doctrines, I review the impact of the Theory of Populism (developed by Ernesto Laclau) on the study of social movements. Populism proposes an adequate framework of political and social inclusion to analyze those marginalized masses intending to construct their own identity and mobilize. Finally, the paper reflects on whether or not the generation of a collective identity is a crucial requirement for the emergence of a social movement.